Describing the elephant the different faces of IT as service. - Foster, Ian (New York ACM, 2005)
In a well-known fable, a group of blind men are asked to describe an elephant. Each encounters a different part of the animal and, not surprisingly, provides a different description.We see a similar degree of confusion in the IT industry today, as terms such as service-oriented architecture, grid, utility computing, on-demand, adaptive enterprise, data center automation, and virtualization are bandied about. As when listening to the blind men, it can be difficult to know what reality lies behind the words, whether and how the different pieces fi t together, and what we should be doing about the animal(s) that are being described. (Of course, in the case of the blind men, we did not also have marketing departments in the mix!)Our goal in this article is to provide, in effect, a description of the elephant. More specifi cally, we describe what we see as a major technology trend that is driving many related efforts--namely, the transformation from vertically integrated silos to horizontally integrated, service-oriented systems. We explain how various popular terms relate to this overarching trend and describe the technology required to realize this transformation.
Keywords: Computing Milieux; Management of computing and information systems; System management; Centralization/Decentralization.; Computer systems organization; System architectures; Computer communication networks; Distributed systems; Distributed applications; Software; Software engineering; Software architectures; Domain specific architectures; Information systems; Information storage and retrieval; Systems and software; On-line information systems; Web-based services; Management